Inhibition of BRD4 attenuates cardiomyocyte apoptosis via NF‐κB pathway in a rat model of myocardial infarction. Issue 2 (8th February 2018) - Sun, Yiping; Xie, Ying; Du, Luping; Sun, Jingwu; Liu, Zhiqiang
Summary: Background: Myocardial infarction (MI) remains the most common cause of heart failure (HF) worldwide. For almost 50 years, HF has been recognized as a determinant of adverse prognosis after MI, but efforts to promote myocardial repair have failed to be translated into clinical therapies. Aims: In this study, we investigated the effects of BRD4 on cardiac function and the underlying mechanism. Material and Methods: The in vivo rat model of AMI and in vitro neonatal cardiomyocytes were established and cultured respectively, the BRD4 and NPPA/NPPB expression levels were detected by qPCR and Western blot, and interaction of BRD4 with acetylation RelA or NPPA/B promoters were examined by co‐immunoprecipitation and chromatin immunoprecipitation assays, respectively. Results: We found that BRD4 protein expression was significantly increased in cardiomyocytes of MI rat model and cardiomyocytes under hypoxia, accompanied by the expression of natriuretic peptide A (NPPA) and natriuretic peptide B (NPPB). Functionally, knockdown of BRD4 greatly downregulated the NPPA and NPPB in vivo and in vitro, improved the hemodynamic and biometric parameters in rat with heart failure, as well as decreased the apoptosis occurrence. In vitro studies further demonstrated that BRD4 bound with acetylated RelA to enhance the activation of NF‐κb signaling, which resulted in activation of NPPA and NPPB transcriptions. Conclusions: Taken together, our findings suggest that inhibition of BRD4 attenuated cardiomyocyte apoptosis via NF‐κB pathway in myocardial infarction, and this study sheds light on developing new strategies to overcome myocardial damage.